Prosedur mengeluar dan menguatkuasa fatwa di semenanjung Malaysia - Hasnan Kasan, (Fakulti Undang - Undang, 2006)

(untitled)
Every activity of a muslim in Malaysia should be bound by fatwa. The religious authority has the authority to issue, declare and enforce the fatwa for an activity which is regarded as important. However there are individuals who questioned the fatwa. Among the reason given is that the authorised individual did not understand the procedure and process of the enforcement of fatwa. This article discusses the procedure which has been laid down by the legislature in the process of issuing, declaring and enforcing a particular fatwa until it is given the status of law which can be enforced and prosecuted on those who disobey the fatwa. This discussion includes those who are involved in declaring the fatwa, the procedure of issuing, declaring and the authority of the fatwa which has been issued and enforced